Thyroid Heart Disease Presenting Thyrotoxic Crisis with Jaundice - Moh. Yahya Al-Hilal Yahya; Mega Memory Rahasa Putra; Khoirotul Ummah (Clinical and Research Journal in Internal Medicine, 2023)
Hyperthyroid can cause thyroid crisis that a rare endocrinal emergency. Jaundice in thyroid heart disease and hyperthyroid patient was very rare. This case we present a patient with thyroid heart disease presenting thyroid crisis and jaundice. A 49-year-old with complaints of shortness of breath at night accompanied by a feeling of weakness. The patient felt tremor in her upper extremity, lost weight, difficulty sleeping and easily tired in the last 2 months. She said that her eyer become yellow in color 10 days ago. On admission the vital signs are blood pressure 130/80 mm Hg, pulse 120x/min, respiration rate 24x/min, O2 saturation 80% on room air, temperature 36.8°C. Physical examination showed icteric, jugular vein pressure was +3 cm and from palpation examination found nodule ±4cm in diameter, well-defined, chewy consistency. Extremities showed tremor and edema. Electrocardiography showed atrial tachycardia and chest x-ray imaging showed cardiomegaly and minimal pleural effusion. Thyroid hormone evaluation showed increase Free T4 and decrease TSH level. Liver function test showed increase bilirubin level. Patient received Propylthiouracil 4x300 mg, Propranolol 4x20mg, normal saline 0.9% Infusion 1000ml/24 hours, Pantoprazole Injection 2x40 mg, Furosemide 10 mg/hour, Spironolactone 1x100mg, Albuforce 2x1 tab, Injection of Ceftriaxone 2x1 gr and referred to RS Soetomo, Surabaya for further treatment Percutaneous Transhepatic Biliary Drainage.